Beginning PHP and MySQL From Novice to Professional - Gilmore, W Jason; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
Beginning PHP and MySQL: From Novice to Professional, Third Edition offers a comprehensive introduction to two of the most prominent open-source technologies on the planet: the PHP scripting language and the MySQL database server. Updated to introduce the features found in MySQL's most significant release to date, readers will learn how to take advantage of the features of both technologies to build powerful, manageable, and stable web applications. Essentially three books in one, readers will not only profit from extensive introductions to the core features of each technology, but also learn how to effectively integrate the two in order to build robust data-driven applications. Packed with practical examples and insight into the real-world challenges faced by developers based on author W. Jason Gilmore's seven years of expertise working with these technologies, readers will repeatedly return to this book as both a valuable instructional tool and reference guide.
Introducing PHP -- Configuring Your Environment -- PHP Basics -- Functions -- Arrays -- Object-Oriented PHP -- Advanced OOP Features -- Error and Exception Handling -- Strings and Regular Expressions -- Working with the File and Operating System -- PEAR -- Date and Time -- Forms -- Authenticating Your Users -- Handling File Uploads -- Networking -- PHP and LDAP -- Session Handlers -- Templating with Smarty -- Web Services -- Secure PHP Programming -- SQLite -- Building Web Sites for the World -- MVC and the Zend Framework -- Introducing MySQL -- Installing and Configuring MySQL -- The Many MySQL Clients -- MySQL Storage Engines and Datatypes -- Securing MySQL -- Using PHP with MySQL -- Introducing PDO -- Stored Routines -- MySQL Triggers -- MySQL Views -- Practical Database Queries -- Indexes and Searching -- Transactions -- Importing and Exporting Data.
Keywords: Software engineering; Software Engineering/Programming and Operating Systems